Thermobar: An open-source Python3 tool for thermobarometry and hygrometry - Wieser, Penny; Petrelli, Maurizio; Lubbers, Jordan; Wieser, Eric; Ozaydin, Sinan; Kent, Adam; Till, Christy (Volcanica, 2022)
We present Thermobar, a new open-source Python3 package for calculating pressures, temperatures, and melt compositions from mineral and mineral-melt equilibrium. Thermobar allows users to perform calculations with >100 popular parametrizations involving liquid, olivine-liquid, olivine-spinel, pyroxene only, pyroxene-liquid, two pyroxene, feldspar-liquid, two feldspar, amphibole only, amphibole-liquid, and garnet equilibria. Thermobar is the first open-source tool which can match up all possible pairs of phases from a given region, and apply various equilibrium tests to identify pairs from which to calculate pressures and temperatures (e.g. pyroxene-liquid, two pyroxene, feldspar-liquid, two feldspar, amphibole-liquid). Thermobar also contains functions allowing users to propagate analytical errors using Monte-Carlo methods, convert pressures to depths using different crustal density profiles, plot mineral classification and mineral-melt equilibrium diagrams, calculate liquid viscosities, and convert between oxygen fugacity values, buffer positions and Fe speciation in a silicate melt. Thermobar can be downloaded using pip and extensive documentation is available at https://thermobar.readthedocs.io/.